Structure, morphology and thermal characteristics of banana nano fibers obtained by steam explosion - Deepa, B.; Abraham, Eldho; Cherian, Bibin Mathew [UNESP]; Bismarck, Alexander; Blaker, Jonny J.; Pothan, Laly A.; Leão, Alcides Lopes [UNESP]; de Souza, Sivoney Ferreira [UNESP]; Kottaisamy, M. (Elsevier B.V., 2011)
In this work, cellulose nanofibers were extracted from banana fibers via a steam explosion technique. The chemical composition, morphology and thermal properties of the nanofibers were characterized to investigate their suitability for use in bio-based composite material applications. Chemical characterization of the banana fibers confirmed that the cellulose content was increased from 64% to 95% due to the application of alkali and acid treatments. Assessment of fiber chemical composition before and after chemical treatment showed evidence for the removal of non-cellulosic constituents such as hemicelluloses and lignin that occurred during steam explosion, bleaching and acid treatments. Surface morphological studies using SEM and AFM revealed that there was a reduction in fiber diameter during steam explosion followed by acid treatments. Percentage yield and aspect ratio of the nanofiber obtained by this technique is found to be very high in comparison with other conventional methods. TGA and DSC results showed that the developed nanofibers exhibit enhanced thermal properties over the untreated fibers. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cellulose nanofibers; Steam explosion; Thermal characteristics; Atomic force microscopy (AFM); Scanning electron microscopy (SEM)